Study guides

Q: 8x2 minus 13x minus 6

Write your answer...

Submit

Related questions

(8x + 3)(x - 2)

6x^2 -13x+6 = (3x-2)(2x-3) when factorized

(x + 3)(5x - 2)

-6 = 3 x -2 13 = 5 x 3 - 2 → 5x² + 13x - 6 = (5x - 2)(x + 3)

If you mean: 13*(x -1) +6 then it is 13x -13 +6 = 13x -7 as an expression

x + 13x + 10x = 50 - 6

5x-13x+6=0 5x-13x=-6 -8x=-6 -8x/-8=-6/-8 x = 3/4

( 8x2 - 14x - 30 ) divided by ( 2x - 6 ) = 4x + 5

If you mean what is 5x2-13x-6 when factored then it is: (5x+2)(x-3) otherwise the GCF is 1

Provided that x- 2 is not zero: 2x3 + x2 - 13x + 6 = 2x3 - 4x2 + 5x2 - 10x - 3x + 6 = 2x2*(x - 2) + 5x*(x - 2) - 3*(x - 2) = (x - 2)*(2x2 + 5x - 3) Therefore, (2x3 + x2 - 13x + 6)/(x - 2) = (x - 2)*(2x2 + 5x - 3)/(x - 2) = 2x2 + 5x - 3 If x = 2 so that x - 2 = 0, then the expression is not defined.

42 + x2 = 13x ∴ x2 - 13x + 42 = 0 ∴ (x - 6)(x - 7) = 0 ∴ x ∈ {6, 7}

If you mean: 4x-6+5x = 13x-8 then it works out that x = 1/2 or 0.5

(x-2)*(2x2+5x-3) Multiply out the brackets term by term taking care with the minus terms:- 2x3-4x2+5x2-10x-3x+6 Collect like terms:- Answer: 2x3+x2-13x+6

6(13x + 6)

Eight minus fourteen is minus six.

78 = 60 + 18 = 13 x 6

x = -1.

If that's + 6, that factors to (3x - 2)(2x - 3)

The answer will be 21x + 1

This is a quadratic equation question which will have two answers: 2x2+42 = x2+13x 2x2-x2-13x+42 = 0 x2-13x+42 = 0 Factorising the equation gives you: (x-6)(x-7) = 0 Therefore: x = 6 or x = 7

13(1)-7(1)=6.

minus 6 is smaller.

-6--3=3

-6 x -3 = 18 + (-6) = 12

(x - 6)(x - 7)